Design sheet and its manufacturing method
By creating an entangled body of ultrafine fibers and forming a resin film with dispersed openings, the design sheet achieves a sparkling, glittery surface with improved productivity and aesthetic appeal, addressing the limitations of previous artificial leather technologies.
Patent Information
- Application Number
- JP2021003019
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-12
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2041-01-12
AI Technical Summary
Existing methods for creating artificial leather with a glittery surface, such as applying pearl pigment or mixing fibers with different fineness, are complex and result in low productivity and unevenness, while silver-like leather sheets lack a rich, design-rich luster.
A design sheet with a glittery surface is achieved by forming an entangled body of ultrafine fibers with an average fineness of 0.005-0.5 dtex, melting the surface fibers to create a resin film containing 95% or more of the resin film, and dispersing openings in an irregular island-like shape to enhance breathability and glitteriness.
The resulting design sheet exhibits a sparkling, glittery surface with excellent surface gloss and breathability, overcoming the productivity and uniformity issues of previous methods while providing a rich, design-enhancing aesthetic.
Smart Images

Figure 0007671146000002 
Figure 0007671146000003 
Figure 0007671146000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a design sheet having a glittery surface. [Background technology]
[0002] Conventionally, artificial leathers are known that are obtained by surface-treating a raw artificial leather including a nonwoven fabric impregnated with polyurethane. For example, grained artificial leathers are obtained by laminating a grain-like resin layer on the surface of the raw artificial leather, and napped artificial leathers are known that have a napped surface formed by napping the fibers forming the surface layer of the raw artificial leather like suede. Such artificial leathers are preferably used as surface materials for bags, shoes, clothing, furniture, car seats, miscellaneous goods, etc.
[0003] In the case of napped artificial leather, artificial leather with a napped surface exhibiting a glossy feel has been proposed. For example, the following Patent Document 1 discloses a suede-like artificial leather in which a napped layer consisting of ultrafine fibers of 0.5 denier or less is formed on the surface of a substrate consisting of a fiber fabric and an elastic polymer impregnated therein, and the suede-like artificial leather is dyed, in which pearl pigment is fixed in spots on the surface of the napped layer by a binder resin, and the shortest distance between each spot and its adjacent spot is 50 to 500 μm. Patent Document 1 discloses that such suede-like artificial leather exhibits a pearl-like glossy feel with the napped surface covered with napped ultrafine fibers.
[0004] In addition, the following Patent Document 2 discloses an artificial leather that is composed of a nonwoven fabric containing a fiber layer containing modified cross-section fibers and a polymeric elastomer impregnated into the nonwoven fabric, and satisfies the following conditions (1) to (5): (1) the fiber layer containing modified cross-section fibers contains, by weight, 10 to 50% modified cross-section fibers and 90 to 50% non-modified cross-section fibers; (2) the degree of irregularity of the modified cross-section fibers is 1.1 to 5.0, and the degree of irregularity of the non-modified cross-section fibers is less than 1.1; (3) the single fiber fineness of the modified cross-section fibers is 0.6 to 5.5 dtex; (4) the titanium oxide content of the modified cross-section fibers is 0.3% or less by weight; (5) the titanium oxide content of the non-modified cross-section fibers is 0.5 to 3.0% by weight. Patent Document 2 discloses that such an artificial leather has a locally shiny surface and has an elegant surface quality.
[0005] Incidentally, a technique has been proposed for producing grain-finished artificial leather by fusing and integrating ultrafine long fibers in the surface layer of the artificial leather greige with a polymeric elastomer, although this technique does not form a napped surface that exhibits a glossy feel. Specifically, for example, the following Patent Document 3 discloses a grain-finished leather-like sheet in which a fused layer is formed on the surface of a leather-like sheet made of an entangled nonwoven fabric in which fiber bundles containing a plurality of ultrafine long fibers are entangled and a polymeric elastomer contained therein, and in which the ultrafine fibers and the polymeric elastomer are fused to each other. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 10-168764 [Patent Document 2] JP 2018-178271 A [Patent Document 3] JP 2010-229603 A Summary of the Invention [Problem to be solved by the invention]
[0007] In the case of the method of applying a pearl pigment to the napped surface as disclosed in Patent Document 1, there was a problem that the productivity was low because the application of the pearl pigment was complicated. In addition, in the case of the method of forming a napped surface having a locally shiny and elegant surface quality by mixing an irregular cross-section fiber and a non-irregular cross-section fiber as disclosed in Patent Document 2, there was a problem that the process was complicated because fibers with different finenesses had to be mixed, and unevenness was likely to occur, resulting in low productivity. In addition, in the case of a grain-finished leather-like sheet in which a fusion layer formed by fusing long ultrafine fibers and a polymeric elastomer as disclosed in Patent Document 3, a fusion layer that is a homogeneous grain-finished film was formed on the surface, so there was no glossy feeling rich in design.
[0008] An object of the present invention is to provide a decorative sheet having a surface with a glittery appearance. [Means for solving the problem]
[0009] One aspect of the present invention is a fiber bundle entanglement comprising ultrafine fibers having an average fineness of 0.005 to 0.5 dtex, the ultrafine fibers being fused to the surface. Melted and fused Ultrafine fibers formed by mixing The fusion product and a number of openings exposing ultrafine fibers that are surrounded by the resin film and dispersed in irregular islands. The average diameter of the openings is 0.5 to 150 μm, and the area ratio of the openings on the surface is 5 to 50%. This is a decorative sheet. The resin film formed by melting ultrafine fibers has a glossy appearance, and there are many irregular island-like openings that do not have a glossy appearance and are mixed in with the resin film, resulting in a sheet with a glittery surface. The openings also enhance the glittery appearance and ensure breathability.
[0010] In addition, the resin film is made of ultra-fine fibers. The fusion productBy containing 95% by mass or more, a resin film with excellent surface gloss is formed. The raw material for artificial leather may contain a polymer elastomer such as polyurethane. When a polymer elastomer is contained in the formation of the resin film, the ultrafine fibers and the polymer elastomer are not compatible with each other and are fused together, which reduces the film-forming ability of the resin film and reduces the gloss. Therefore, the resin film is difficult to form due to the incompatibility of the ultrafine fibers such as the polymer elastomer. Other than the fusion The outer ingredients 5% by mass Preferably, 1% by mass More preferably, the resin film does not contain more than The fusion product By using only this, a resin film having a superior gloss can be obtained.
[0011] Moreover, it is preferable that the area ratio of the openings in the surface is 10 to 30%, since this allows the formation of a surface with a more lustrous feel.
[0012] As for the size of the openings, it is preferable that the average diameter of the openings is 1 to 100 μm, since a highly uniform glittery feel can be obtained.
[0013] The average thickness of the resin film is preferably 50 to 100 μm in order to form appropriate openings.
[0014] Another aspect of the present invention is a method for producing any of the decorative sheets described above, comprising the steps of: preparing an entangled body made of fiber bundles of ultrafine fibers having an average fineness of 0.005 to 0.5 dtex; and heating the surface of the entangled body in a non-contact manner to melt the ultrafine fibers that form the surface of the entangled body. Melting and Melting Wear This forms a large number of openings and resin films. and a process for forming a tangled The surface area is within 200 μm from the surface of the coalescence. The voids in the layer are filled with of ultrafine fibers In contrast 5% by mass This is a manufacturing method of a decorative sheet that does not contain other components as described above. By using this manufacturing method, the decorative sheet as described above can be easily obtained. Effect of the Invention
[0015] According to the present invention, a decorative sheet having a glittery surface can be obtained. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a scanning electron microscope (SEM) photograph at 50x magnification of the surface of the design sheet obtained in Example 1. [Diagram 2] FIG. 2 is an SEM photograph at a magnification of 50 times of a cross section parallel to the thickness direction of the design sheet obtained in Example 1. [Diagram 3] FIG. 3 is a SEM photograph at a magnification of 50 times of the surface of the grain-finished artificial leather obtained in Comparative Example 1. [Figure 4] FIG. 4 is an SEM photograph at 40x magnification of a cross section parallel to the thickness direction of the design sheet obtained in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The decorative sheet of the present embodiment includes an entangled body made of fiber bundles of ultrafine fibers having an average fineness of 0.005 to 0.5 dtex, and has ultrafine fibers fused to the surface. Fusing and welding The ultra-fine fibers formed by The fusion product The decorative sheet has a resin film containing 95% by mass or more of the above-mentioned fiber and a large number of openings that expose ultrafine fibers that are surrounded by the resin film and dispersed in irregular islands.
[0018] Refer to the SEM photograph of the design sheet obtained in Example 1 described later, which is an example of the design sheet of this embodiment. Figure 1 is an SEM photograph of the surface of the design sheet obtained in Example 1 at a magnification of 50 times, and Figure 2 is an SEM photograph of the cross section parallel to the thickness direction at a magnification of 50 times.
[0019] 1 and 2, the design sheet 10 of this embodiment includes an entangled nonwoven fabric, which is an entangled body made of fiber bundles 1a of ultrafine fibers 1 having an average fineness of 0.005 to 0.5 dtex, and has a resin film 1b formed on the surface by melting the ultrafine fibers 1 and a large number of openings v that expose the ultrafine fibers 1 that are surrounded by the resin film 1b and dispersed in the shape of irregular islands. A plurality of ultrafine fibers 1 derived from ultrafine fiber-generating fibers described below form the fiber bundles 1a. The openings are the parts of the surface of the design sheet where no resin film is formed.
[0020] The resin membrane essentially dissolves the microfibers. Melted and fused The resin film is formed by mixing 95% by mass or more, preferably 99% by mass or more, and more preferably 100% by mass of the resin film is made of ultrafine fibers. The fusion product Ultrafine Fiber The fusion product By containing 95% by mass or more of the above, a resin film with excellent surface gloss is formed. General artificial leather raw materials may contain polymeric elastomers such as polyurethane. When a large amount of other components such as polymeric elastomers are contained in the formation of the resin film, the film-forming properties and gloss are reduced. Therefore, the resin film is formed by mixing the resin components that form the ultrafine fibers. The fusion product It is essentially free of ingredients other than those listed below. Specifically, 5% by mass Less than, preferably is 1% by mass If the thickness is less than 100 nm, a resin film having a superior glossiness can be obtained.
[0021] The average thickness of such a resin film is preferably 10 to 200 μm, more preferably 50 to 100 μm, since openings of an appropriate size are formed and a glittery appearance with excellent aesthetics is presented.
[0022] 1, the decorative sheet 10 of this embodiment has numerous openings v that expose the ultrafine fibers 1 that are surrounded by the resin film 1b and dispersed in irregular islands. In these numerous openings v, the ultrafine fibers 1 in the inner layer of the decorative sheet 10 are exposed and do not exhibit gloss. On the surface, the resin film 1b that exhibits gloss and the openings v that do not exhibit gloss are mixed together, resulting in a sparkling, glittery appearance with glossy parts dispersed therein.
[0023] The openings are surrounded by the resin film and are dispersed in the form of irregular islands. Here, irregular means that the outlines of the openings are not the same. The average diameter of such openings is 0.5 to 150 μm. m, 1 It is preferable that the diameter is 100 μm or less. If the diameter of the opening is too large or too small, the surface tends to have a non-uniform glittery feel. The diameter of the opening is the diameter of a circle having the same area as the area of the opening.
[0024] The ratio of the opening area to the surface area is 5 to 50. %, and 1 A ratio of 0 to 30% is preferable because it provides a more aesthetically pleasing glittering effect. If the area ratio of the openings is too low, the surface becomes similar to a continuous film such as a grain-finish resin layer, and the glittering effect is reduced. If the area ratio of the openings is too high, the surface becomes similar to the napped surface of raised artificial leather, and the glittering effect is reduced. The area ratio of the openings is determined by taking a SEM photograph of the surface at 50 times magnification, determining the ratio of the openings to the entire surface, and calculating the average value of 15 evenly selected points.
[0025] As described above, the design sheet of this embodiment includes an entangled fiber bundle made of ultrafine fibers having an average fineness of 0.005 to 0.5 dtex. Such an entangled fiber bundle made of ultrafine fibers is an entangled fiber bundle of ultrafine fibers having an average fineness of 0.005 to 0.5 dtex formed by producing an entangled fiber of ultrafine fiber generating fibers such as sea-island type composite fibers and subjecting the ultrafine fiber generating fibers to an ultrafine fiber processing. Examples of the entangled body include nonwoven fabrics, woven fabrics, knitted fabrics, and entangled bodies of combinations thereof. Among these, nonwoven fabrics are preferred because they can provide a design sheet with a particularly excellent surface appearance.
[0026] The average fineness of the ultrafine fibers is 0.005 to 0.5 dtex, preferably 0.007 to 0.3 dtex. If the average fineness of the ultrafine fibers exceeds 0.5 dtex, the ultrafine fibers are difficult to melt quickly, making it difficult to form a resin film with excellent gloss and difficult to obtain a soft texture. If the average fineness of the ultrafine fibers is less than 0.005 dtex, the ultrafine fibers are melted too quickly, making it difficult to form appropriate openings and making it easy to form a continuous film.
[0027] In the design sheet of this embodiment, it is preferable that the voids of the entangled body are not impregnated with a large amount of a polymeric elastomer such as polyurethane. Even if the polymeric elastomer is contained, the polymeric elastomer is not substantially contained in the vicinity of the surface layer where the resin film is formed, specifically, in the range of 200 μm or even 500 μm from the surface, and preferably the content ratio of the polymeric elastomer is 5% by mass Less than or even 1% by mass It is preferable that the content of the polymer elastomer is less than 0 mass %, and particularly 0 mass %. Therefore, when other components such as a polymer elastomer are added to the voids of the entanglement body, , and ultrafine fibers combined On the other hand 5% by mass Less than, or even 3% by mass Hereinafter, preferably 1% by mass It is preferable that:
[0028] A representative example of the manufacturing method for the design sheet of this embodiment described above will be described below.
[0029] The design sheet of this embodiment is manufactured, for example, by the following process. First, ultrafine fiber-generating fibers for forming fiber bundles of ultrafine fibers, specifically, for example, an entanglement of sea-island type composite fibers from which ultrafine fiber bundles consisting of island components are formed by removing the sea component, are manufactured. Then, an entanglement of ultrafine fiber bundles is formed by subjecting the ultrafine fiber-generating fibers to ultrafine fiber processing, and the thickness is adjusted by slicing or buffing as necessary. Then, the thickness-adjusted entanglement of ultrafine fiber bundles is dyed as necessary. Then, at least one surface of the dyed entanglement of ultrafine fiber bundles is heated in a non-contact manner to melt and fuse the ultrafine fibers forming the surface of the entanglement. In this way, the design sheet of this embodiment is manufactured. Each process will be described in detail below.
[0030] (1) Manufacturing of entangled fibers that generate ultrafine fibers In this embodiment, a method for producing an entangled body of islands-in-sea type composite fibers will be described in detail as a method for producing an entangled body of ultrafine fiber-generating fibers. Note that ultrafine fiber-generating fibers other than islands-in-sea type composite fibers may be used as the ultrafine fiber-generating fibers. Specific examples of ultrafine fiber-generating fibers other than islands-in-sea type composite fibers include peel-split type fibers formed by lightly bonding multiple ultrafine fibers immediately after spinning and then untangling the multiple ultrafine fibers by mechanical operations, and petal-shaped fibers formed by alternately assembling multiple resins in a petal-like shape in a melt spinning process.
[0031] In the production of an entangled island-in-sea type composite fiber, a web of islands-in-sea type composite fibers is first produced by melt spinning. In a later appropriate step, the sea part of the islands-in-sea type composite fiber is extracted or decomposed to remove the sea part, thereby forming fiber bundles of ultrafine fibers consisting of island parts.
[0032] Examples of the method for producing the web include a method using a so-called spunbond method, in which islands-in-the-sea composite fibers are spun by melt spinning and collected on a net without cutting to form a long fiber web, and a method for collecting short fibers cut to an arbitrary fiber length (for example, 18 to 110 mm) and stapled to form a short fiber web. Among these, the use of a long fiber web is preferred because it is easy to give a higher glittery feel and to obtain a surface with a large number of openings surrounded by the resin film and dispersed in an irregular island shape. In this embodiment, the production of a long fiber web will be described in detail as a representative example.
[0033] Examples of thermoplastic resins that form the island components of the islands-in-the-sea composite fiber and form the ultrafine fibers include fibers formed from synthetic resins with fiber-forming ability, such as polyester-based resins such as polyethylene terephthalate (PET), polytrimethylene terephthalate, polybutylene terephthalate (PBT), and polyester elastomers; polyamide-based resins such as polyamide 6, polyamide 66, polyamide 610, aromatic polyamides, and polyamide elastomers; acrylic resins; and olefin resins. Among these, PET, particularly modified PET whose melting point (softening temperature) is lowered by modification treatment, is preferred because it is easy to form a resin film by melting and fusing the thermoplastic resin that forms the ultrafine fibers. As the modified PET, modified PET containing asymmetric aromatic carboxylic acids such as isophthalic acid, phthalic acid, and 5-sodium sulfoisophthalic acid, and aliphatic dicarboxylic acids such as adipic acid, as copolymerization components in a predetermined ratio, is preferred. More specifically, modified PET containing 2 to 12 mol % of isophthalic acid units as a monomer component is particularly preferred.
[0034] The average cross-sectional area of islands-in-the-sea composite fiber is 30 to 800 μm 2 The average area ratio (corresponding to the polymer volume ratio) of the sea part to the island part in the cross section of the islands-in-sea type composite fiber is preferably 5 / 95 to 70 / 30. The number of islands in the islands-in-sea type composite fiber, which is the same as the number of ultrafine fibers constituting the fiber bundle, is not particularly limited, but is preferably 5 to 1,000, more preferably 10 to 300.
[0035] In the case of modified PET after spinning, the melting point peak of the crystal domain is, for example, around 90 to 130°C. Therefore, by heating to a temperature near the peak top of the melting point peak, the modified PET starts to soften. By heating the nap surface at a temperature higher than the melting point peak by non-contact heating described later, the thermoplastic resin forming the ultrafine fiber melts and forms a resin film, and a large number of voids are formed in the part surrounded by the resin film, and openings are formed in a dispersed manner. The melting point (softening temperature) of the crystal domain is measured by a differential scanning calorimeter (DSC). The melting point peak is the peak top of the endothermic peak measured when 10 mg of ultrafine fiber is sealed and placed in an aluminum pan and heated from 5°C to 250°C at a rate of 10°C / min.
[0036] On the other hand, specific examples of the thermoplastic resin forming the sea part of the islands-in-sea type composite fiber include polyvinyl alcohol, polyethylene, polypropylene, polystyrene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, styrene-ethylene copolymer, styrene-acrylic copolymer, etc.
[0037] The islands-in-sea type composite fibers are preferably spun and the web is formed by a spunbonding method. Specifically, a composite spinning die having a large number of nozzle holes arranged in a predetermined pattern is used to continuously extrude the islands-in-sea type composite fibers from each nozzle hole onto a moving net in the form of a conveyor belt, and the fibers are deposited while being cooled by a high-speed air current. A web of islands-in-sea type composite fibers is formed by such a method.
[0038] The web is then stacked and entangled in about 4 to 100 layers using a cross wrapper or the like to form an entangled web of islands-in-sea composite fibers. The entangled web is formed by entanglement of the web using a known nonwoven fabric manufacturing method such as needle punching or high-pressure water flow treatment. For example, in the case of entanglement by needle punching, a silicone-based oil or a mineral oil-based oil such as an oil for preventing needle breakage, an antistatic oil, or an oil for improving entanglement is first applied to the web. Then, an entanglement treatment is performed by needle punching to entangle the fibers three-dimensionally. The punching density is, for example, 300 to 6000 punches / cm.2 , and even 500~4500 punches / cm 2 By subjecting the web to entanglement treatment, an entangled web having a high fiber density and less susceptible to fiber shedding can be obtained.
[0039] If necessary, the entangled web may be immersed in hot water at 70 to 150°C to heat shrink the entangled web, thereby increasing the fiber density and the degree of entanglement of the entangled web. Specific examples of the heat shrinkage treatment include a method of continuously contacting the entangled web with water vapor, and a method of applying water to the entangled web and then heating the water applied to the entangled web with heated air or electromagnetic waves such as infrared rays. In this manner, an entangled body of islands-in-sea type composite fibers is obtained.
[0040] (4) Ultrafine fiber formation process The islands-in-sea composite fibers in the entangled body of islands-in-sea composite fibers are converted into ultrafine fibers in the form of fiber bundles by dissolving or decomposing and removing the sea component. For example, in the case of islands-in-sea composite fibers using water-soluble polyvinyl alcohol as the sea component, the water-soluble polyvinyl alcohol as the sea component is dissolved and removed by performing dip nip treatment multiple times in hot water at 85 to 100°C. Also, for example, in the case of islands-in-sea composite fibers using polyethylene as the sea component, the polyethylene is dissolved and removed by immersing in an organic solvent such as toluene, trichloroethylene, or tetrachloroethylene. In this way, an entangled body of ultrafine fiber bundles with an average fiber diameter of 1 to 10 μm is formed.
[0041] (5) Thickness adjustment process The thickness of the entangled fiber bundles of ultrafine fibers is adjusted as necessary by slicing them into a plurality of pieces, grinding the surface, etc. The thickness of the entangled fiber bundles after the thickness adjustment is not particularly limited, but is preferably, for example, 0.3 to 3.0 mm, and more preferably, 0.6 to 1.5 mm.
[0042] (6) Dyeing process The thus obtained napped artificial leather substrate is usually preferably dyed. Dyeing is performed by appropriately selecting a dye based on disperse dyes, cationic dyes, reactive dyes, acid dyes, metal complex dyes, sulfur dyes, sulfur vat dyes, etc. according to the type of fiber, and using a known dyeing machine that is usually used for dyeing fibers, such as a padder, jigger, circular, or wince. For example, when the ultrafine fiber is a polyester fiber, it is preferable to dye it by high-temperature and high-pressure dyeing using a disperse dye. In addition, when the dyeing process is performed, it is preferable to provide a washing process before or after any process after the dyeing process in order to increase fastness.
[0043] (7) A process for melting and fusing the ultrafine fibers forming the surface by non-contact heating of the surface of the entangled fiber bundle of ultrafine fibers. The surface of the entangled body of ultrafine fiber bundles is heated in a non-contact manner to melt and fuse the ultrafine fibers forming the surface of the entangled body. By such a process, a surface is formed that has a resin film formed by melting the ultrafine fibers and a large number of openings that expose the ultrafine fibers that are surrounded by the resin film and dispersed in irregular islands, as described above.
[0044] Here, non-contact heating is a treatment in which the object to be treated is heated in a non-contact state without directly contacting the object to be treated with a heating roller, a hot plate, or the like. Examples of such non-contact heating include a method of using a flame burner or an electric heater to heat the object to be treated without directly contacting the heat source to the surface of the object to be treated. When using a flame burner, city gas, propane gas, LPG gas, or the like can be used as fuel. Examples of the flame burner include an industrial gas burner used for singeing the surface of a fiber fabric, or a flame lamination burner used when laminating a foam. Examples of the electric heater include a high-temperature hot air heater, a far-infrared heater, and a heat-reflecting electric heater. Among these, a flame lamination burner is preferred because it can obtain a stable melting state of the object to be treated and can increase the processing speed.
[0045] The shape of the resin film is appropriately adjusted depending on the type of non-contact heating, the distance from the heat source, the heating time, and the like.
[0046] After non-contact heating, the treated surface is, if necessary, appropriately smoothed with a cooled embossing roller or flat roller, etc., to form a smooth and glossy resin film.
[0047] In this way, the design sheet of the present embodiment is obtained. The thickness of the design sheet is not particularly limited, but is preferably 0.6 to 1.5 mm. The apparent density of the design sheet is preferably 0.3 to 0.7 g / cm. 3 , and even 0.4 to 0.6 g / cm 3 Such a design sheet has a surface that gives a glittery shine due to the reflection of light from the multiple resin films that are appropriately dispersed. Such a design sheet is preferably used for shoes, which place importance on design and breathability, and for bags, interior decoration, and the like, which place importance on design. EXAMPLES
[0048] The present invention will be described in more detail below with reference to examples. Note that the scope of the present invention is not limited to these examples. First, the evaluation methods used in the examples will be summarized below.
[0049] (Average fineness of ultrafine fibers) When a cross section of the design sheet cut parallel to the thickness direction was photographed at 500 times magnification using a scanning electron microscope (SEM), the area of the ultrafine fibers cut perpendicular to the fiber axis direction was measured, the average area was calculated, and the diameter of a circle with the same area was calculated. The average value of 15 evenly selected points was then calculated as the average fiber diameter. The average fiber diameter was then converted to an average fineness based on the density of the IPA-modified PET that forms the ultrafine fibers.
[0050] (Observation of surface condition and cross section) The surface of the resulting design sheet was observed at 50x magnification using an SEM. The area ratio of the openings and the average diameter of the openings were determined from the SEM photographs of the surface. The area ratio of the openings was the average value of the area ratios determined from 15 evenly selected SEM photographs. The average diameter of the openings was determined by converting the areas of the openings observed in the 15 evenly selected SEM photographs into the diameter of the same circle and averaging the results. In addition, a cross section of the resulting design sheet cut parallel to the thickness direction was observed with an SEM at 40 to 50 magnifications. The thickness of the resin film formed on the surface was measured at a total of 10 points at 100 μm intervals. The average value was then calculated. The average thicknesses identified in the SEM photographs of 15 evenly selected points were then further averaged to obtain the average thickness. Figure 1 shows an example of an SEM photograph at 50 times the surface of the design sheet obtained in Example 1, and Figure 4 shows an example of an SEM photograph at 50 times the surface of the design sheet obtained in Comparative Example 1. For reference, Figure 2 shows an SEM photograph at 40 times the cross section of the design sheet obtained in Example 1 cut parallel to the thickness direction, and Figure 4 shows an SEM photograph at 40 times the cross section of the design sheet obtained in Comparative Example 1 cut parallel to the thickness direction.
[0051] (Glittery surface) The appearance of the surface was visually inspected by 10 monitors engaged in the manufacture of artificial leather, and the glitteriness of the surface was judged by majority vote based on the following criteria. A: It has a high level of glitter. B: Moderate amount of shimmer. C: Has a low shimmer feel. D: No glitter.
[0052] (Texture) A test piece measuring 20 cm x 20 cm was cut from the design sheet. The texture of the test piece was then evaluated according to the following criteria. A: It had a soft texture. B: It had a hard texture.
[0053] [Example 1] Water-soluble thermoplastic polyvinyl alcohol (PVA) was prepared as the sea component, and isophthalic acid-modified polyethylene terephthalate (IPA-modified PET, melting point (peak softening point 135°C)) with a modification degree of 6 mol% was prepared as the island component. The sea component and island components were then fed into a composite spinning spinneret set at a spinneret temperature of 260°C and having nozzle holes arranged in parallel, each nozzle hole forming a cross section in which 25 island components with uniform cross-sectional areas were distributed in the sea component resin, and molten strands were extruded from the nozzle holes. At this time, the pressure was adjusted while feeding so that the mass ratio of the sea component to the island components was sea component / island component = 25 / 75.
[0054] The molten strand was then drawn by sucking with a suction device at an average spinning speed of 3700 m / min, to spin an islands-in-sea type composite fiber with a diameter of 20 μm. The islands-in-sea type composite fiber was continuously deposited on a movable net, and lightly pressed with a metal roll at 42°C to suppress surface fuzzing. The islands-in-sea type composite fiber was then peeled off from the net, and passed between a lattice-patterned metal roll and a back roll at a surface temperature of 75°C and a linear pressure of 200 N / mm. In this way, a fiber with a basis weight of 31 g / m was obtained. 2 The web was manufactured.
[0055] Next, the web is wrapped with a cross wrapper to a total weight of 250 g / m 2 A stacked web was made of eight layers so that the number of layers was 8, and a needle breakage prevention oil was sprayed on the stacked web. Then, using a six-barb needle with a distance from the needle tip to the first barb of 3.2 mm, the stacked web was punched alternately from both sides at a needle depth of 8.3 mm at 3,300 punches / cm. 2 By needle punching, the weight is 320g / m 2 The islands-in-the-sea type composite fiber entanglement was produced. The islands-in-the-sea type composite fiber entanglement was then taken up and immersed in hot water at 70°C for 14 seconds at a line speed of 10 m / min to cause area shrinkage. The entangled fibers were then repeatedly subjected to dip nip treatment in hot water at 95°C to dissolve and remove the modified PVA, resulting in a fiber bundle containing 25 ultrafine long fibers of IPA-modified PET and three-dimensionally entangled fiber bundles with a basis weight of 480 g / m 2 , apparent density 0.52g / cm 3 A nonwoven fabric was produced from the IPA-modified PET fiber bundles.
[0056] The fiber bundle entangled nonwoven fabric was adjusted to a thickness of 0.82 mm by buffing, then dyed brown with a disperse dye of 5% owf in a liquid jet dyeing machine and dried. In this way, a design sheet greige was obtained.
[0057] Then, using a flame lamination burner, the flame of a gas burner was evenly applied to the surface of the design sheet greige to fuse the ultrafine fibers, and immediately thereafter, the surface was pressed with a metal roll to smoothen it. The gas burner used city gas as fuel, and processing was performed at a conveying speed of 10 m / min. In this way, a design sheet was manufactured. The design sheet had an apparent density of 0.65 g / cm 3 The weight is 530g / m 2 The design sheet was then evaluated as described above.
[0058] The results are shown in Table 1 below.
[0059] [Table 1]
[0060] [Example 2] A decorative sheet was produced in the same manner as in Example 1, except that the number of islands of the ultrafine fiber island component was changed from 25 to 12 islands to produce an entangled nonwoven fabric of fiber bundles. The decorative sheet had an apparent density of 0.65 g / cm 3 The basis weight is 600g / m 2 The resulting design sheet was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0061] [Example 3] A decorative sheet was produced in the same manner as in Example 1, except that the number of islands in the ultrafine fiber island component was changed from 25 to 50, and an entangled nonwoven fabric of fiber bundles was produced. The decorative sheet had an apparent density of 0.67 g / cm 3 The basis weight is 600g / m 2 The resulting design sheet was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0062] [Example 4] In the same manner as in Example 1, an entangled nonwoven fabric of fiber bundles of IPA-modified PET was produced. The thickness of the entangled nonwoven fabric was adjusted to 0.82 mm by buffing, and then dyed brown with a disperse dye of 5% owf in a liquid flow dyeing machine and dried to obtain a fiber base material. The fiber base material was then impregnated with a polyurethane emulsion so as to be uniform in the thickness direction, and then dried to obtain a design sheet greige. At this time, the mass ratio of the entangled nonwoven fabric to the polyurethane was 96:4. The polyurethane emulsion had a soft segment consisting of a mixture of polyhexylene carbonate diol and polymethyl pentane diol in a ratio of 70:30, a hard segment consisting mainly of hydrogenated methylene diisocyanate, and a polyurethane with a melting point of 180 to 190°C.
[0063] Then, in the same manner as in Example 1, the flame of a gas burner was evenly applied to the surface of the design sheet greige to fuse the ultrafine fibers, and immediately thereafter, the surface was pressed with a metal roll to smoothen the surface to obtain a design sheet. On the surface of the obtained design sheet, a grain-finish resin film was formed, which was a continuous film formed by fusing IPA-modified PET and polyurethane. The obtained design sheet had an apparent density of 0.63 g / cm 3 The weight is 520g / m 2 The resulting design sheet was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0064] [Example 5] A decorative sheet was produced in the same manner as in Example 1, except that the number of islands in the ultrafine fiber island component was changed from 25 to 200 and an entangled nonwoven fabric was produced. The decorative sheet had an apparent density of 0.70 g / cm 3 The basis weight is 600g / m 2 The resulting design sheet was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0065] [Comparative Example 1] A decorative sheet was produced in the same manner as in Example 4, except that the mass ratio of the entangled nonwoven fabric and the polyurethane was changed to 90:10. The decorative sheet had an apparent density of 0.63 g / cm 3 The weight is 510g / m 2 The resulting design sheet was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0066] [Comparative Example 2] Except for changing the mass ratio of the entangled nonwoven fabric to polyurethane to 80:20, a decorative sheet was produced in the same manner as in Comparative Example 1. The obtained decorative sheet was then evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0067] [Comparative Example 3] A decorative sheet was produced in the same manner as in Example 1, except that only island components were extruded from the nozzle holes and fibers with a diameter of 15 μm were spun to produce an entangled nonwoven fabric. The decorative sheet had an apparent density of 0.45 g / cm. 3 The basis weight is 600g / m 2 The resulting design sheet was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0068] The design sheets obtained in Examples 1 to 5 all had a surface with a glittery feel. On the other hand, the design sheets obtained in Comparative Examples 1 to 3 did not have a glossy resin film formed by melting the ultrafine fibers. In the design sheets of Comparative Examples 1 and 2, it is believed that the polyurethane present on the surface layer inhibited the formation of a homogeneous resin film. In addition, in the design sheet of Comparative Example 3, the ultrafine fibers were too thick, so the ultrafine fibers did not melt sufficiently to the inside, and a homogeneous resin film was not formed, and the resin film and the ultrafine fibers were in a mixed state, so the thickness of the resin film could not be measured. [Explanation of symbols]
[0069] 1. Ultrafine Fiber 1a Fiber bundle 1b Resin film 10 Design sheet v opening
Claims
1. The fiber bundles include an entanglement of ultrafine fibers having an average fineness of 0.005 to 0.5 dtex, The present invention is provided with a resin film formed on a surface thereof by melting and fusing the ultrafine fibers, the resin film containing 95% by mass or more of the fused ultrafine fibers, and a large number of openings through which the ultrafine fibers are surrounded by the resin film and dispersed in the form of irregular islands are exposed, A design sheet characterized in that the average diameter of the openings is 0.5 to 150 μm, and the area ratio of the openings to the surface is 5 to 50%.
2. The design sheet according to claim 1, wherein the area ratio of the openings on the surface is 10 to 30%.
3. The design sheet according to claim 1 or 2, wherein the average diameter of the openings is 1 to 100 μm.
4. The design sheet according to any one of claims 1 to 3, wherein the average thickness of the resin film is 50 to 100 μm.
5. A method for producing the design sheet according to any one of claims 1 to 4, A step of preparing an entangled body composed of fiber bundles of ultrafine fibers having an average fineness of 0.005 to 0.5 dtex; and a step of non-contact heating the surface of the entangled body to melt and fuse the ultrafine fibers forming the surface of the entangled body to form a large number of the openings and the resin film, A method for producing a decorative sheet, characterized in that the voids in the surface layer, which are within 200 μm from the surface of the entangled body, do not contain other components that amount to 5% by mass or more in total with respect to the ultrafine fibers of the surface layer.
Citation Information
Patent Citations
JP1973019924B1
Peccary-like artificial leather and production thereof
JP1984199873A
Silvered artificial leather and its production
JP1985034676A
Suedelike artificial leather having pearly luster
JP1998168764A
Grained leathery sheet and method for producing the same
JP2005002481A